2008
DOI: 10.1111/j.1582-4934.2008.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference‐mediated silencing of the polo‐like kinase 1 gene enhances chemosensitivity to gemcitabine in pancreatic adenocarcinoma cells

Abstract: Gemcitabine is the first-line chemotherapeutic agent for advanced adenocarcinoma of the pancreas; however, chemoresistance to gemcitabine remains a major cause of failure for the clinical treatment of this disease. Polo-like kinase 1 (Plk-1) is highly expressed in pancreatic cancer cell lines and pancreatic tumour tissues, and is involved in a wide variety of cell cycle processes. Nevertheless, its biological role and implication for gemcitabine resistance are not clearly defined. In this study, we used RNA-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…A separate analysis found Plk1 mRNA and protein to be overexpressed in clinical pancreatic cancer samples and in cell lines but more importantly decreasing Plk1-induced growth arrest in preclinical models (14). Yu et al showed recently that treatment of pancreatic cancer cells with Plk1 siRNA followed by exposure to gemcitabine dramatically decreased cell viability and increased cellular apoptosis compared with treatment with either agent alone (19).…”
Section: Discussionmentioning
confidence: 99%
“…A separate analysis found Plk1 mRNA and protein to be overexpressed in clinical pancreatic cancer samples and in cell lines but more importantly decreasing Plk1-induced growth arrest in preclinical models (14). Yu et al showed recently that treatment of pancreatic cancer cells with Plk1 siRNA followed by exposure to gemcitabine dramatically decreased cell viability and increased cellular apoptosis compared with treatment with either agent alone (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a nonadenosine triphosphate competitive (18) and an adenosine triphosphate-competitive inhibitor (19) have both progressed into Phase I clinical testing. Other groups have successfully knocked down Plk1 using small interfering ribonucleic acids (siRNAs), resulting in decreased in vitro growth of bladder (20) and prostate cancer cells (21), as well as increased chemosensitivity in pancreatic cancers (22). To date, no one has investigated such an approach for head-and-neck squamous cell carcinoma (HNSCC).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that silencing of the PLK-1 gene can enhance chemosensitivity to gemcitabine in pancreatic adenocarcinoma cells (34). Notably, we found that the mRNA level of PLK-1 was also increased in SP cells.…”
Section: Discussionmentioning
confidence: 50%